Relationship between binge drinking experience and suicide attempts in Korean adolescents: based on the 2013 Korean Youth Risk Behavior Web-based Survey - Kyeong Hyang Byeon; Sun Ha Jee; Jae Woong Sull; Bo Young Choi; Heejin Kimm (Epidemiology and Health, 2018)
OBJECTIVES Suicide and drinking problems in adolescents are increasing every year, and it is known that suicide is related to drinking. This study aims to identify the relationship between binge drinking experience (BDE) and suicide attempts in Korean adolescents. METHODS The Ninth Korean Youth Risk Behavior Web-based Survey (KYRBS), conducted in 2013, was used for analysis. Multiple logistic regression analysis was used to identify the relationship between BDE and suicide attempts, and the relationship between BDE and suicide attempts in middle and high school students was stratified by age. RESULTS BDE and suicide attempts were highly related. The odds ratio (OR) of attempted suicide in BDE was 1.63 times (95% confidence interval [CI], 1.28 to 2.09) higher then non-drinking in males. And the OR of attempted suicide in females was 1.21 times (95% CI, 1.07 to 1.37) higher then non-drinking in non-BDE, 1.79 times (95% CI, 1.47 to 2.19) higher in BDE. BDE was associated with suicide attempts in males aged 12 or 13 years (OR, 3.97; 95% CI, 1.57 to 10.03) and in females aged 15 years (OR, 2.66; 95% CI, 1.79 to 3.96). CONCLUSIONS BDE is an important factor related to suicide attempts in adolescents. In order to reduce suicide attempts, it is necessary to educate the youth about the regulation of BDE and drinking prevention.